Clinical course features of atypical demyelinating optic neuritis: case series - Sheremet, N. L.; Eliseeva, D. D.; Bryukhov, V. V.; Andreeva, N. A.; Zhorzholadze, N. V.; Murakhovskaya, Yu. K.; Kalashnikova, A. K.; Zakharova, M. N. (Nevrologii͡a︡, neĭropsikhiatrii͡a︡, psikhosomatika, 2023)
Optic neuritis (ON) can often occur at the onset of a demyelinating autoimmune CNS disease or as one of its clinical manifestations. The introduction of novel laboratory techniques, technical advances in magnetic resonance imaging (MRI), electrophysiologic studies, and ocular imaging have significantly expanded the spectrum of autoimmune optic neuropathies. Identification of different forms of ON based on clinical and instrumental data can lead to early diagnosis of the underlying neurologic disorder. According to current guidelines, one can distinguish between typical ON, which are mainly associated with multiple sclerosis (MS), and atypical ON, which are the main clinical manifestation of neuromyelitis optica spectrum disorders (NMOSD) and diseases associated with myelin oligodendrocyte glycoprotein antibodies (MOGAD). In this paper, we present four clinical cases of atypical ON at the onset of NMOSD and MOGAD and illustrate the high diagnostic value of a multidisciplinary approach.